Osteocyte Apoptosis Contributes to Cold Exposure-induced Bone Loss - Du, Jingke; He, Zihao; Cui, Junqi; Li, Hanjun; Xu, Mingming; Zhang, Shuhong; Zhang, Shuangyan; Yan, Mengning; Qu, Xinhua; Yu, Zhifeng (Frontiers in Bioengineering and Biotechnology, 2021)
Emerging evidence indicates that bone mass is regulated by systemic energy balance. Temperature variations have profound effects on energy metabolism in animals, which will affect bone remodeling. But the mechanism remains unclear. 2-month-old C57BL/6J male mice were exposed to cold (4°C) and normal (23°C) temperatures for 28 days and the effects of cold exposure on bone mass was investigated. Micro-computed tomography results showed that bone volume fraction was significantly reduced after 14 days of exposure to cold temperature, and it was recovered after 28 days. Ploton silver staining and immunohistochemical results further revealed that exposure to cold decreased canalicular length, number of E11-and MMP13-positive osteocytes after 14 days, but they returned to the baseline levels after 28 days, different from the normal temperature control group. In addition, change of Caspase-3 indicated that exposure to cold temperature augmented apoptosis of osteocytes. In vitro results confirmed the positive effect of brown adipocytes on osteocyte‘s dendrites and E11 expression. In conclusion, our findings indicate that cold exposure can influence bone mass in a time-dependent manner, with bone mass decreasing and recovering at 2 and 4 weeks respectively. The change of bone mass may be caused by the apoptosis osteocytes. Brown adipocyte tissue could influence bone remodeling through affecting osteocyte.